2023
DOI: 10.3389/fncir.2023.1124221
|View full text |Cite
|
Sign up to set email alerts
|

Practice makes plasticity: 10-Hz rTMS enhances LTP-like plasticity in musicians and athletes

Abstract: Motor skill learning has been linked to functional and structural changes in the brain. Musicians and athletes undergo intensive motor training through the practice of an instrument or sport and have demonstrated use-dependent plasticity that may be subserved by long-term potentiation (LTP) processes. We know less, however, about whether the brains of musicians and athletes respond to plasticity-inducing interventions, such as repetitive transcranial magnetic stimulation (rTMS), differently than those without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Another possible mechanism by which transcranial magnetism improves cognitive function is the mechanism of long-term enhanced plasticity. Transcranial magnetism in healthy musicians and athletes can improve learning and exercise performance by promoting LTP-like activation of key networks ( 51 ). Li et al’s ( 52 ) study showed that using transcranial magnetic stimulation at a frequency of 20 Hz to the dorsolateral prefrontal cortex (DLPFC) of Alzheimer’s patients significantly increased the amplitude of motor evoked potentials at different time periods, with a significant difference in change rate compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism by which transcranial magnetism improves cognitive function is the mechanism of long-term enhanced plasticity. Transcranial magnetism in healthy musicians and athletes can improve learning and exercise performance by promoting LTP-like activation of key networks ( 51 ). Li et al’s ( 52 ) study showed that using transcranial magnetic stimulation at a frequency of 20 Hz to the dorsolateral prefrontal cortex (DLPFC) of Alzheimer’s patients significantly increased the amplitude of motor evoked potentials at different time periods, with a significant difference in change rate compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulator device was a CCY-I TMS instrument with a Cool-B80 butterfly coil (Yiruide Co., Wuhan, China). By reviewing relevant literature, about the use of 10 Hz rTMS, there was stimulation for 1.5 s with intervals of 58.5 s ( 16 ) and stimulation for 4 s with intervals of 26 s ( 17 ). In our study, we aimed to compare the efficacy of the 10 Hz rTMS and the iTBS; hence, the same number of pulses (900 pulses) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the stimulation frequency, rTMS can either increase or decrease the excitability of the stimulated brain region [ 48 ]. High-frequency rTMS can enhance synaptic strength and excitability, potentially leading to long-term potentiation (LTP)—a mechanism associated with learning and memory [ 49 ]. Spatial and temporal specificity: The effects of TMS depend on factors such as the intensity, frequency, and duration of the magnetic pulses.…”
Section: Basic Theory Of Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Focal stimulation: TMS allows for focal stimulation of specific brain regions depending on the coil’s placement. Effects on synaptic plasticity: TMS has been shown to induce changes in synaptic plasticity, influencing the strength of connections between neurons [ 49 ]. This can lead to both short-term and long-term effects on neural circuits.…”
Section: Basic Theory Of Transcranial Magnetic Stimulationmentioning
confidence: 99%